Ways to effectively organize the circulation of corporate securities in the financial market - Jo’rayev Og’abek Oybek o’gli (Zien Journals, 2023)
The article examines the prospects of introducing financial technologies in the stock market. Based on the results of the research work, scientific conclusions are presented on the effective organization of the emission of securities in the development of the financial market and on the increase and development of its role in the economy.
Keywords: the economic nature of the financial market; financial technologies in the securities market; prospects for the introduction of the securities market